Making 'Postmodern' Mothers - Nash, M. author. aut Link
IX, 247 p.
Keywords: Based on interviews with pregnant women, this book provides a multi-disciplinary empirical account of pregnant embodiment and how it relates to wider sociological and feminist discourses about gender, bodies, 'fitness', 'fat', celebrity and motherhood.